Acute morphine induces matrix metalloproteinase-9 up-regulation in primary sensory neurons to mask opioid-induced analgesia in mice - Liu Yen-Chin; Berta Temugin; Liu Tong; Tan Ping-Heng; Ji Ru-Rong (SAGE Publishing, 2012)
Abstract Background Despite decades of intense research efforts, actions of acute opioids are not fully understood. Increasing evidence suggests that in addition to well-documented antinociceptive effects opioids also produce paradoxical hyperalgesic and excitatory effects on neurons. However, most studies focus on the pronociceptive actions of chronic opioid exposure. Matrix metalloproteinase 9 (MMP-9) plays an important role in neuroinflammation and neuropathic pain development. We examined MMP-9 expression and localization in dorsal root ganglia (DRGs) after acute morphine treatment and, furthermore, the role of MMP-9 in modulating acute morphine-induced analgesia and hyperalgesia in mice. Results Subcutaneous morphine induced a marked up-regulation of MMP-9 protein in DRGs but not spinal cords. Morphine also increased MMP-9 activity and mRNA expression in DRGs. MMP-9 up-regulation peaked at 2 h but returned to the baseline after 24 h. In DRG tissue sections, MMP-9 is expressed in small and medium-sized neurons that co-express mu opioid receptors (MOR). In DRG cultures, MOR agonists morphine, DAMGO, and remifentanil each increased MMP-9 expression in neurons, whereas the opioid receptor antagonist naloxone and the MOR-selective antagonist <smcaps>D</smcaps>-Phe-Cys-Tyr-<smcaps>D</smcaps>-Trp-Arg-Thr-Pen-Thr-NH2 (CTAP) suppressed morphine-induced MMP-9 expression. Notably, subcutaneous morphine-induced analgesia was enhanced and prolonged in Mmp9 knockout mice and also potentiated in wild-type mice receiving intrathecal injection of MMP-9 inhibitors. Consistently, intrathecal injection of specific siRNA targeting MMP-9 reduced MMP-9 expression in DRGs and enhanced and prolonged morphine analgesia. Subcutaneous morphine also produced heat hyperalgesia at 24 h, but this opioid-induced hyperalgesia was not enhanced after MMP-9 deletion or inhibition. Conclusions Transient MMP-9 up-regulation in DRG neurons can mask opioid analgesia, without modulating opioid-induced hyperalgesia. Distinct molecular mechanisms (MMP-9 dependent and independent) control acute opioid-induced pronociceptive actions (anti-analgesia in the first several hours and hyperalgesia after 24 h). Targeting MMP-9 may improve acute opioid analgesia.